Measuring outcomes in cataract surgery. Issue 1 (January 2018) - Qin, Vivian L.; Conti, Felipe F.; Singh, Rishi P.
Abstract : Purpose of review: The article presents a review of recently published studies reporting postcataract surgery outcomes and the use of electronic systems to track them. Recent findings: Current publications report several parameters to measure cataract outcomes such as visual acuity, patient-reported visual function, contrast sensitivity, reading speed, residual refractive errors and complications (intraoperative and postoperative). Summary: Cataracts currently afflict an estimated 94 million people worldwide, and surgical removal is the only effective therapy known. Tracking outcomes through registry databases has been shown to be a powerful tool for improving patient outcomes, understanding and adopting best clinical practices, reducing costs and increasing value delivered. Large datasets present in electronic registry systems are valuable resources for evaluating the quality of care by allowing researchers and healthcare providers to analyze, understand and adjust to 'real-world' best practices and adverse events.